Design as a Promoter of Consumer Society Comfort - Dias Maximo, Fabio Henrique; Monteiro de Oliveira, Luísa; Urban Bernardes de Menezes, Rodrigo Octávio; Carpintero Rezende, Edson José (DAT Journal, 2020)
Sometimes design produces goods that satisfy the individual’s desires just by consumption. The current socioeconomic system is based on the assumption that mass production can provide individuals with an increase in their quality of life through the consumption of products and services. In this panorama, we will discuss the configuration of the consumer society and the contributions of design to well-being. The discussion will take place on two fronts: to demonstrate how the sense of well-being and comfort were modified by the trade in products and services and; to point out how the planning of design projects contributes to the maintenance of this socioeconomic system based on consumption. The discussion in this article seeks to demonstrate that economic growth, industrial development and increased production that makes new products feasible and that facilitates the access of these goods to the whole society does not provide the much desired social well-being of a population.